2019
DOI: 10.17651/bptj.74.3
|View full text |Cite
|
Sign up to set email alerts
|

Źródła w tworzeniu elektronicznego słownika paradygmatów frazeologizmów werbalnych

Abstract: Celem artykułu jest wskazanie typów źródeł i sposobów ich wykorzystania przy opracowywaniu słownika paradygmatów frazeologizmów czasownikowych. Autorzy charakteryzują wykorzystywane źródła, omawiają użyteczność źródeł słownikowych i korpusowych (w zależności od etapu prac nad słownikiem) oraz ich ograniczenia. Szczególną uwagę poświęcają roli introspekcji w tworzeniu słownika gramatycznego.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Contemporary lexicography has become electronic to a significant extent, which is a consequence of the use of computers in linguistic studies, a tendency that has been observed for several decades at different stages of compiling a dictionary. Text corpora 1 , which are the source of linguistic units that are recorded and whose meanings are isolated, play a crucial role in the process (Kosek et al 2018). The effect of technology and computers is also seen in gathering and storing information necessary to produce a dictionary.…”
mentioning
confidence: 99%
“…Contemporary lexicography has become electronic to a significant extent, which is a consequence of the use of computers in linguistic studies, a tendency that has been observed for several decades at different stages of compiling a dictionary. Text corpora 1 , which are the source of linguistic units that are recorded and whose meanings are isolated, play a crucial role in the process (Kosek et al 2018). The effect of technology and computers is also seen in gathering and storing information necessary to produce a dictionary.…”
mentioning
confidence: 99%